Role of the complement system in antibody-dependent enhancement of flavivirus infections. (February 2021) - Byrne, Alana B.; Talarico, Laura B.
Highlights: Pathogenic and protective effects of complement in flavivirus infections. Protective role of classical pathway activation on ADE of flavivirus infections. Binding of human IgG isotypes to C1q depends on Fc domain flexibility and conformation. C1q modulation of ADE of flavivirus infections by different potential mechanisms. Abstract: Flavivirus infections have increased dramatically in the last decades in tropical and subtropical regions of the world. Antibody-dependent enhancement of dengue virus infections has been one of the main hypotheses to explain severity of disease and one of the major challenges to safe and effective vaccine development. In the presence of cross-reactive sub-neutralizing concentrations of anti-dengue antibodies, immune complexes can amplify viral infection in mononuclear phagocytic cells, triggering a cytokine cascade and activating the complement system that leads to severe disease. The complement system comprises a family of plasma and cellular surface proteins that recognize pathogen associated molecular patterns, modified ligands and immune complexes, interacting in a regulated manner and forming an enzymatic cascade. Pathogenic as well as protective effects of complement have been reported in flavivirus infections. This review provides updated knowledge on complement activation during flavivirus infection, including antiviral effects of complement and its regulation, as well as mechanisms of complement evasion and dysregulation of complement activity during viral infection leading to pathogenesis. Particularly, insights into classical pathway activation and its protective role on antibody-dependent enhancement of flavivirus infections are highlighted.